1996
DOI: 10.1021/jf950370k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of Atrazine, Deethylatrazine, Deisopropylatrazine, and Hydroxyatrazine on Levy Wetland Soil

Abstract: The adsorption and desorption of atrazine, and its three metabolites, deethylatrazine (DEA), deisopropylatrazine (DIA), and hydroxyatrazine (HA), on Levy wetland soil were measured using the batch equilibration technique. Solution concentrations for each chemical were 1.3, 3.8, 6.6, and 13.2 μmol L-1. Four 24-h period desorptions for each concentration were conducted immediately after adsorption. The adsorption of all the chemicals conformed to linear isotherms. Adsorption coefficients decreased in the order H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
8
46
0
7
Order By: Relevance
“…Vegetative growth in forest wetland ecosystems is often limited by N and P. Nutrients that are taken up by plants and microbes are supplied through nutrient mineralization during the litter decomposition process (Koch and Reddy 1992;Cooper and Brush 1993). In the past few decades, intensive agricultural fertilization and inadequate wastewater treatment have contributed to increasing concentrations of N (Smolen 1981;Magette et al 1989;Pickett et al 1992;Hill 1996) and herbicides (Kolpin et al 1994;Liu et al 1996;Pasquarell and Boyer 1996) in surface runoff and groundwater which in some cases have resulted in the accumulation of these chemicals in wetlands (Szeto et al 1990;Spalding et al 1994;Goolsby et al 1994;Wan et al 1994Wan et al , 1995Mersie and Seybold 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative growth in forest wetland ecosystems is often limited by N and P. Nutrients that are taken up by plants and microbes are supplied through nutrient mineralization during the litter decomposition process (Koch and Reddy 1992;Cooper and Brush 1993). In the past few decades, intensive agricultural fertilization and inadequate wastewater treatment have contributed to increasing concentrations of N (Smolen 1981;Magette et al 1989;Pickett et al 1992;Hill 1996) and herbicides (Kolpin et al 1994;Liu et al 1996;Pasquarell and Boyer 1996) in surface runoff and groundwater which in some cases have resulted in the accumulation of these chemicals in wetlands (Szeto et al 1990;Spalding et al 1994;Goolsby et al 1994;Wan et al 1994Wan et al , 1995Mersie and Seybold 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is it very laborious to determine K oc , but also the measured K oc is very dependent on the properties of used soil. Here the log K oc values of the four herbicides determined by Mersie and Seybold (1996) with a kind of soil are presented in Table 2, accompanied with their aqueous solubilities (Erickson and Lee 1989). Shea (1989) suggested that K oc values were negatively correlated with aqueous solubilities for the same class of compounds.…”
Section: Resultsmentioning
confidence: 95%
“…Vários autores têm mostrado a maior retenção do metabólito HA em relação a atrazina e aos outros metabólitos, DEA e DIA (Clay & Koskinen, 1990;Brower et al, 1990;Mersie & Seybold, 1996;Lerch et al, 1999), o que tem sido atribuído à menor solubilidade em água da HA e a sua maior estabilidade termodinâmica (Erickson & Lee, 1989;Lerch et al, 1999). Isto também foi observado neste trabalho.…”
Section: Profundidade (Cm)unclassified
“…Os valores do parâmetro N, para sorção, foram de 0,84 e 0,85 para PD e PC, respectivamente, mostrando isotermas de sorção não lineares para a atrazina, nas concentrações empregadas. A magnitude destes valores está de acordo com a literatura (Clay & Koskinen, 1990;Mersie & Seybold, 1996;Moreau & Mouvet, 1997;Mersie et al, 1999) e sugere um grau de sorção intermediário para a atrazina, quando comparada com moléculas altamente sorvidas (por exemplo, o glifosato e os organoclorados -Prata et al, 2000b;Roberts & Hudson, 1999, respectivamente) ou de sorção reduzida (por exemplo, o picloram e o aldicarb - Roberts et al, 1998;Roberts & Hudson, 1999 Freundlich para dessorção. 6/ Grau de linearidade da isoterma de sorção.…”
Section: Sorção E Dessorçãounclassified
See 1 more Smart Citation